An identification of authentic narrator's name features in Malay hadith texts - Abd Rahman N.; Alias N.; Ismail N.K.; Bin Mohamed Nor Z.; Alias M.N.B. (Institute of Electrical and Electronics Engineers Inc., 2024)
Indexed by Scopus/WOS